European Revolution and Post-recovery Health and Disease - Muhammad Furqan; Miftahul Rizki; Rizka Rosalia; Shyllatulal Aita (Yayasan Yusda Edu Indonesia, 2026)
The French Revolution was one of the most influential events in European and modern world history. It not only ended absolute monarchy in France but also gave rise to new ideas about popular sovereignty, human rights, and the principle of equality before the law. This article aims to examine the background of the French Revolution, the social, political, and economic conditions that underpinned it, the dynamics of the Consulate and Napoleonic Empire, and the revolution's impact on the European order. This research uses a literature review method with a historical-analytical approach. The results show that the French Revolution was the result of structural inequality, a state financial crisis, and the influence of Enlightenment thought. While bringing advances in the legal system and modern government, the revolution also gave rise to political violence and instability. The conclusion of this study confirms that the French Revolution marked the beginning of modern Europe, albeit at a significant social and humanitarian cost.